KAJIAN FILOSOFIS TERHADAP MULTIKULTURALISME INDONESIA - Irhandayaningsih, Ana (HUMANIKA, 2012)
Multiculturalism is both an ideology and a means to create egalitarian and peaceful relationship between cultural groups in Indonesia. But there are some problems found when we analyze its basic assumptions, i.e. the principle of egality and recognition of differences. Firstly, a tension happens between ‘one and many’, where multiculturalism ironically will neglect similarities while emphasizing differences among cultural groups. Secondly, conflicts may arise between claims of egality of minorities. If we want to proceed with the multicultural agenda, we need to solve these problems. Keywords: multiculturalism, egality, recognition, minorities